Career Identification of Production Operators’ Position in Manufacture Industries - Romadin, Achmad; Yoto, Yoto; Nurhadi, Didik (Fakultas Teknik Universitas Negeri Malang, 2021)
Graduating of Vocational High School in the manufacturing industry occupies job of production position. The demands of industrial needs are in the manufacturing sector. They want employees or labor that have told and professional competencies. Therefore, it is necessary to analyze and identify career in operator position. This study uses qualitative research. This research focuses on analysis of operator's position needs in the industry. Based on the results of the research, the work of production operators includes briefing, setting, operating, quality procedures, and engine maintenance. There are several competencies regarding the position of production operators, namely occupational health and safety, quality assurance, measuring instruments, hand tools, technical drawings, general machining, and special conditions. Production operators get salaries, which include grade-based salaries, and salary holidays. Susceptible salary obtained by production operator position gets a vulnerable salary based on the industrial area district minimum wage where he works.